"And Yet, It Moves": Intergenerational Mobility in Italy - Paolo Acciari; Alberto Polo; Giovanni L. Violante (Institute of Labor Economics (IZA), 2019)
We link administrative data on tax returns across two generations of Italians to study the degree of intergenerational mobility. We estimate that a child with parental income below the median is expected to belong to the 44th percentile of its own income distribution as an adult, and the probability of moving from the bottom to the top quintile of the income distribution within a generation is 0.10. The rank-rank correlation is 0.25, and rank persistence at the top is significantly higher than elsewhere in the income distribution. Upward mobility is higher for sons, first-born children, children of self-employed parents, and for those who migrate once adults. The data reveal large variation in child outcomes conditional on parental income rank. Part of this variation is explained by the location where the child grew up. Provinces in Northern Italy, the richest area of the country, display upward mobility levels 3-4 times as large as those in the South. This regional variation is strongly correlated with local labor market conditions, indicators of family instability, and school quality.
Keywords: J31; J61; J62; R1; 330; intergenerational mobility; inequality; Italy; geographical variation